2011
DOI: 10.1038/onc.2011.472
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal prostaglandin E synthase-1 is involved in multiple steps of colon carcinogenesis

Abstract: Accumulating evidence indicates that cyclooxygenase (COX)-2-derived prostaglandin (PG) E 2 is involved in the development of various tumors, including colorectal cancer. However, the precise contribution of microsomal PGE synthase (mPGES)-1, a terminal enzyme that acts downstream of COX-2 in the PGE 2 -biosynthetic pathway, to multiple processes of tumor development is not yet fully understood. Here, we show the pro-tumorigenic role of mPGES-1 in chemical carcinogen-induced colon carcinogenesis and intraspleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 49 publications
6
49
0
Order By: Relevance
“…COX-2 inhibitors reduce mucosal damage, which further indicates the role of prostaglandins in tissue damage and inflammation reactions (Zheng et al 2012). PTGES catalyzes the isomerization of PGH2 to PGE2, and the latter plays an important role in inflammation (Liu et al 2012a), cell growth, and transformation (Sasaki et al 2012). In the current study, we found that the NF-κB, iNOS, and TNF-α mRNA levels of heart tissue were significantly increased (P < 0.05) in stress groups.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 inhibitors reduce mucosal damage, which further indicates the role of prostaglandins in tissue damage and inflammation reactions (Zheng et al 2012). PTGES catalyzes the isomerization of PGH2 to PGE2, and the latter plays an important role in inflammation (Liu et al 2012a), cell growth, and transformation (Sasaki et al 2012). In the current study, we found that the NF-κB, iNOS, and TNF-α mRNA levels of heart tissue were significantly increased (P < 0.05) in stress groups.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, curcumin deters the conversion of COX-2-derived PGH 2 to PGE 2 (Fig. 19) (Jakobsson et al, 1999;Samuelsson et al, 2007), a reaction that recently was deemed critical in the onset and progression of colorectal cancer (Sasaki et al, 2012). Because of these PG-inhibitory effects, curcumin has been shown to promote cancer cell apoptosis, decelerate angiogenesis, and facilitate the clearance of malignant lesions by the immune system.…”
Section: +mentioning
confidence: 99%
“…Regarding mPGES-1, it participates in various pathophysiological states in which COX-2 is involved. Consistent with the role of mPGES-1 for PGE 2 synthesis, mPGES-1 knockdown has been shown to reduce PGE 2 levels and reduce tumor proliferation and/or invasiveness in several tumor cell types through a EGR1/β-catenin signaling axis (Donnini, Finetti, 2011, Sasaki, Kamei, 2011. The third enzyme involved in PGE 2 homeostasis, 15-PGDH, also plays an important role in carcinogenesis.…”
Section: Several Lines Of Evidence Suggest That Cox-2 Signaling Is Immentioning
confidence: 77%
“…Recently, more evidence has suggested that mPGES-1 participates in various pathophysiological states in which COX-2 is involved. Consistent with the role of mPGES-1 for PGE 2 synthesis, mPGES-1 knockdown has been shown to inhibit PGE 2 production and reduce tumor proliferation and/or invasiveness of several tumor cell types including Lewis lung carcinoma cells, human prostate cancer cell lines and colorectal cancer cells, through a novel EGR1/β-catenin signaling axis (Sasaki et al , 2011).…”
Section: Introductionmentioning
confidence: 81%